Revision of the pulchella-group of Alona s. lato leads to its translocation to Ovalona Van Damme et Dumont, 2008 (Branchiopoda: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2015)
The pulchella-group of Alona s.l. (Cladocera: Anomopoda: Chydoridae) is transferred to Ovalona Van Damme et Dumont, 2008, and an emended diagnosis is provided. Ovalona meridionalis (Sinev, 2006) is removed from Ovalona due to differences in thoracic limb morphology. At the moment, Ovalona consists of 17 species, and is the largest natural genus of Aloninae. A key for the world fauna and diagnosis for all species is provided. The morphology of O. nuragica (Margaritora, 1971) is studied for the first time. The position of Ovalona within subfamily Aloninae and the distribution of the genus are discussed.